Value Chain Analysis to Achieve Competitive Advantage (Survey on MSMEs in Tasikmalaya City) - Rahayu, Intan; Nanda, Ulfa Luthfia (AIBPM Publisher, 2020)
The most important goal of every business is to provide satisfaction to its customers. A business will be profitable if the value obtained is greater than the cost of production and services provided. As one of the icons of the City of Tasikmalaya, the fate of the kelom geulis businessmen is actually getting worse. The invasion of cheap imported sandals and shoes that entered the local market and shops, has made the kelom more marginalized. Even a number of galleries of kelom business actors have closed or switched to selling other products due to the lack of buyers. Value Chain Analysis is one of the strategic tools that companies can use to achieve competitive advantage. Value Chain Analysis is able to identify the internal and external parts of the company, namely the existence of main activities and supporting activities with the ultimate goal of making a profit. This study aims to determine the effect of value chain analysis on the competitive advantage of the company, so that it can provide input and renewal for MSMEs in Tasikmalaya City. This research will be carried out at MSMEs in the city of Tasikmalaya with survey methods and quantitative approaches, and sampling using area sampling techniques. The data source used is primary data, and the data collection technique used is a questionnaire distributed in the form of google form. Hypothesis testing in this study uses simple linear regression analysis.